1993
DOI: 10.1111/j.1432-1033.1993.tb18320.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural requirements for processing of pro‐adipokinetic hormone I

Abstract: We found that a seven‐residue sequence in pro‐adipokinetic hormone I (proAKH I) which precedes the endopeptidase cleavage site is predicted to form an Ω loop. Molecular modelling experiments indicated that a stable Ω loop may form at this site, and suggested that loop stability may depend on the C‐terminal loop residue, Lys12. The importance of this residue in proAKH I processing was confirmed by the observation that replacement of Lys12 by thialysine, a Lys analog with an altered side chain, prevented process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…These data, supported by the study of the processing domain OT/Np(1-20) [59], reveal the presence of b-turn structure in the vicinity of the dibasic cleavage site. These conclusions, confirmed by different studies conducted on the OT/Np [60], Adipokinetic hormone [61] and insulin [62] precursors, support the concept that b-turn structures constitute recognition signals for the processing endoproteases [2,43].…”
supporting
confidence: 84%
“…These data, supported by the study of the processing domain OT/Np(1-20) [59], reveal the presence of b-turn structure in the vicinity of the dibasic cleavage site. These conclusions, confirmed by different studies conducted on the OT/Np [60], Adipokinetic hormone [61] and insulin [62] precursors, support the concept that b-turn structures constitute recognition signals for the processing endoproteases [2,43].…”
supporting
confidence: 84%
“…Earlier analysis of amino acid sequences around proteolytic cleavage sites of several biosynthetic precursors by secondary structure predictive methods (31) indicated that the dibasic residues constituting these cleavage sites are located in or immediately adjacent to regions with high β-turn formation propensity (3,31,53). Site-directed mutagenesis of prohormone cDNA coupled with spectroscopic and enzymatic studies of substrates reproducing the cleavage loci of various prohormones have shown that these β-turn structures situated in the vicinity of dibasic cleavage sites (16,(54)(55)(56)(57)(58) constitute an essential feature for the processing of precursors (14,36,54,57).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of prohormones, it has been postulated that amino acid flanking dibasic cleavage sites and secondary structures may direct endoprotease to the appropriate sites ( ). Studies conducted with short peptides reproducing cleavage sites of prosomatostatin and of prooxytocin/neurophysin have shown that the sequences flanking the basic amino acid doublets might participate in the recognition of the cleavage site by providing accessible peptide segments constituted by β-turns () or Ω-loops ( , ) and may indeed play a role in the processing ( , ). From these studies, it was assumed that such structures, which are flexible and mobile, favor both the accessibility and the segmental adaptability when compared with other structures such as α-helices or β-sheets.…”
Section: Discussionmentioning
confidence: 99%